Optimizing Pregnancy Outcomes: The Role of Gynecologists in Preconceptional Care in Italy - Valensise H; Banzi C; Bonin C; Dell'Avanzo M; Di Simone N; Farsetti D; Manganello F; Mecacci F; Serena C; Villaccio B; Viora E (International Journal of Women's Health, 2025)
Herbert Valensise,1,2 Cristina Banzi,3 Cecilia Bonin,4 Marinella Dell’Avanzo,5 Nicoletta Di Simone,6,7 Daniele Farsetti,1,2 Francesca Manganello,8 Federico Mecacci,9 Caterina Serena,9 Barbara Villaccio,10 Elsa Viora11 1Department of Surgical Sciences, Tor Vergata University, Rome, Italy; 2Division of Obstetrics and Gynecology, Policlinico Casilino, Rome, Italy; 3University Hospital of Ferrara, Ferrara, Italy; 4University of Verona and Azienda Ospedaliera Universitaria Integrata of Verona, Verona, Italy; 5Humanitas San Pio X, Milan, Italy; 6IRCCS Humanitas Research Hospital, Milan, Italy; 7Department of Biomedical Sciences, Humanitas University, Milan, Italy; 8Private Practice, Venezia, Italy; 9Department of Experimental, Clinical and Biomedical Sciences, Obstetrics and Gynecology Unit, Careggi University Hospital, Florence, Italy; 10San Pietro Fatebenefratelli Hospital, Rome, Italy; 11Italian Society of Obstetrics and Gynecology (SIGO), Turin, ItalyCorrespondence: Daniele Farsetti, Division of Obstetrics and Gynecology, Policlinico Casilino, University of Rome Tor Vergata, Via Casilina 1049, Rome, 00169, Italy, Tel +39 3395238927, Email dan.farsetti@gmail.comAbstract: The preconceptional period is crucial for women and couples who desire children as it influences the progress and outcomes of a healthy pregnancy. Preconceptional care is now an accepted paradigm by most healthcare professionals. However, its implementation in healthcare programs is still in the early stages. Preconceptional care starts with communication and a collection of personal and family medical history. It then encompasses a variety of recommendations for lifestyle interventions, as well as preventive laboratory tests. This review will summarize current recommended procedures, from nutritional to disease screening, and their impact on pregnancy outcomes. Folic acid supplementation has been shown to significantly decrease complications such as neural tube defects, and is now widely recommended during the preconceptional phase. Additionally, nutritional supplementation, including the intake of vitamins D and B12, has been linked to healthier pregnancies. Screening for ToRCH infections (toxoplasmosis, syphilis, hepatitis B, rubella, cytomegalovirus, and herpes simplex virus), as well as non-infectious conditions, may help avoid complications during pregnancy. This review will also provide an overview of current practices worldwide, focusing on the Italian context. This document will be helpful to update the medical community, especially gynecologists, on the current knowledge of the benefits of 1) maintaining a healthy nutritional state, including vitamin and mineral supplementation, 2) screening strategies for infectious and non-infectious diseases, and 3) avoiding dangerous behaviors, such as smoking, alcohol consumption, and drug use, for women and couples planning a pregnancy. It also provides suggestions on how to identify such couples to best intervene during the “window of opportunity”. Finally, we aim to provide a simple decalogue, which healthcare professionals can use as a checklist. It can also be delivered directly to women or couples planning a pregnancy, reaching them with straightforward language.Keywords: supplements, genetic screening, disease screening, recommendations, woman’s health